Robert Koch a life in medicine and bacteriology - Brock, Thomas D. 1926-2021 (ASM Press, 2014)
Chronicles the life of Robert Koch, focusing on his contributions to the fields of medicine and bacteriology, discussing his research trips to India, findings on the causes of tuberculosis, cholera, and anthrax, postulates, Nobel Prize, and other related topics
Originally published: Madison, Wis
Includes bibliographical references and index
Keywords: Koch, Robert -- 1843-1910